PENGARUH PERSEPSI MENGENAI KEMUDAHAN MENGGUNAKAN DAN PERSEPSI KEGUNAAN PADA NIAT UNTUK MENGGUNAKAN INTERNET - Rahab Rahab (Faculty of Economics and Business Universitas Jenderal Soedirman, 2009)
The aims of this research are to analyses Perceived Ease to Use and Perceived usefulness to use internet. This research used Structural Equation Modeling (SEM) with Partial Least Square (PLS) with responder SLTP and SLTA teachers in Purwokerto.Results of these research are that perceived ease to use have not effect to intention to use, while perceived usefulness to use internet have effect to intention to use.